Student readiness of a newly-designed blended learning English language proficiency course in UiTM / Nur Fatima Wahida Mohd Nasir - Mohd Nasir, Nur Fatima Wahida (2014)
In the field of education, technology has developed vastly in becoming one of the mainmediums of instruction in schools, institutions or even training programmes. Educators from all over the world are now looking up into new implementations in replacing the old conventional way of teaching to enhance a better learning environment among students in this era of globalization. Special attention is now focusing into what is known as a combination of e-learning and face to face learning (F2F) called blended learning. This paper conducts a study among 156 Diploma undergraduates of the Universiti of Teknologi MARA (UiTM) Shah Alam, Malaysia which aims to investigate on students' readiness in a newly-designed blended learning English language proficiency course under the Academy of Language Studies (ALS) using a reliable and valid questionnaire as the main instrumentation. Moreover, correlation between students' perception of technology as a tool for increasing motivation in learning with their enjoyment going to the new course is also being investigated as well as on the differences of students' readiness between gender, course and semester. Thus, in order to achieve a comprehensive understanding of the study, a mixed method design was developed. Findings indicate that Diploma students of UiTM Shah Alam exhibit above-medium levels of readiness toward blended learning and that there is a significant difference only between semesters. Further recommendations of the research are also discussed in the study.